General algorithm, its mathematical basis and computer autonomic program for calculation of phase diagrams of binary systems, containing p disordered phases of variable and q phases of constant compositions at (p,q) ≤ 10 - Udovsky, A.L.; Karpushkin, V.N.; Kozodaeva, E.A. (Calphad, 1995)
The method of thermodynamic calculation of binary phase diagrams (2PD), containing p disordered phases of variable composition and q phases of constant composition for case (p,q) ≤ 10 was constructed in this paper. In this method 1) the definition of all possible solutions of phase equilibrium equations system (PEES) was realized; 2) the — separation of PEES' roots or tie-line's ends at (T,P) = const was conducted; 3) the original algorithm for calculation of PEES' roots was constructed and programmed and theorems about this algorithm convergence and about behaviour of this convergence were formulated and — proved; 4) the algorithm for autonomic selection of thermodynamically stable tie- lines was constructed and thereby calculating process T-x phase diagrams was automated. Some examples of using this method for calculation of binary phase diagrams for Cr-W, Ni-H, Ni-Al and Ni-Cr are reported here.